Hirohito - Severns, Karen (New York : Chelsea House, 1988)
A biography of the Japanese emperor who, following World War II, approved a constitution that changed his role from divine ruler to "symbol of the state" with political control going to elected representatives.
Cover title: Hirohito.
Includes index.
Bibliography: p. 108.
Keywords: Hirohito, -- Emperor of Japan, -- 1901-1989 -- Juvenile literature; Hirohito, -- Emperor of Japan, -- 1901-1989.; Emperors -- Japan -- Biography -- Juvenile literature; Kings, queens, rulers, etc; Japan -- History -- Showa period, 1926-1989 -- Juvenile literature; Japan -- History -- Showa period, 1926-1989